Targeting Pathological Amyloid Aggregates with Conformation-Sensitive Antibodies - Bigi, Alessandra; Loffredo, Gilda; Cascella, Roberta; Cecchi, Cristina (Current Alzheimer Research, 2020)
Background: The pathogenesis of Alzheimer's disease (AD) is not directly caused by the presence of senile plaques but rather by the detrimental effects exerted on neuronal cells by toxic soluble oligomers. Such species are formed early during the aggregation process of the Aβ1-42 peptide or can be released from mature fibrils. Nowadays, efficient tools for an early diagnosis, as well as pharmaceutical treatments targeting the harmful agents in samples of AD patients, are still missing. Objective: By integrating in vitro immunochemical assay with in vivo neuronal models of toxicity, we aim to understand and target the principles that drive toxicity in AD. Methods: We evaluated the specificity and sensitivity of A11 and OC conformational antibodies to target a range of pathologically relevant amyloid conformers and rescue their cytotoxic effects in neuronal culture models using a number of cellular readouts. Results: We demonstrated the peculiar ability of conformational antibodies to label pathologically relevant Aβ1-42 oligomers and fibrils and to prevent their detrimental effects on neuronal cells. Conclusion: Our results substantially improve our knowledge on the role of toxic assemblies in neurodegenerative diseases, thus suggesting new and more effective diagnostic and therapeutic tools for AD.
Keywords: toxic oligomers